Data Mining Untuk Menerapkan Algoritma Hash Based Pada Penetapan Pola Tata Letak Penjualan Bakery and Cake - Mohammad Aldinugroho Abdullah; Rima Tamara Aldisa (STMIK Budi Darma, 2023)
Bakery and cake business is one of the businesses engaged in the culinary field. bakery and cake business has always been the center of attention for entrepreneurs because it will always have consumers or customers. Usually the bakery and cake business will be in demand when there are events such as birthdays, souvenirs and other events. Bakery and cake is a business that sells various cake or cake products. In determining the layout of each item can affect the efficiency of sales. Because consumers can easily find the items they need. In determining the layout of each item can be used data mining. Data mining is data mining which will eventually be used in digging up various information and producing information, data and knowledge by using pre-existing information. In this study the algorithm used is a hash based algorithm. Hash based algorithm is an algorithm that uses filtering techniques to produce a combination pattern in an itemset. Based on the research results, it was found that the main priority items were G = peanut butter, H = white bread L = srikaya jam with a support value of 25% and 60% confidence. So that peanut butter, srikaya jam and plain bread should coexist in order to increase sales efficiency at bakeries and cake.